2014
DOI: 10.1007/s10517-014-2721-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Survival and Neurological Deficit in Rats in the New Model of Global Transient Cerebral Ischemia

Abstract: We propose a modification to rat model of transient global cerebral ischemia with four-vessel occlusion avoiding pneumothorax and minimizing the consequences of surgery. Survival and neurological deficit in rats in this model was studied over 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The surgery was performed as described previously [ 16 , 72 ]. Briefly, rats were anesthetized with chloral hydrate in a dose of 450 mg/kg intraperitoneally (Sigma-Aldrich Chemical Co., St. Louis, MO, USA) and placed on a homeothermic blanket (Temperature Control Unit HB 101/2, Letica Scientific Instruments, Barcelona, Spain) in a supine position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgery was performed as described previously [ 16 , 72 ]. Briefly, rats were anesthetized with chloral hydrate in a dose of 450 mg/kg intraperitoneally (Sigma-Aldrich Chemical Co., St. Louis, MO, USA) and placed on a homeothermic blanket (Temperature Control Unit HB 101/2, Letica Scientific Instruments, Barcelona, Spain) in a supine position.…”
Section: Methodsmentioning
confidence: 99%
“…At Days 11 and 31 after surgery, neurological deficit was evaluated with the Stroke-index McGraw scale [ 72 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acute global cerebral ischemia was induced according to the new 3-vessel model, as detailed elsewhere [ 30 , 31 ]. Briefly, rats were anesthetized with chloral hydrate in a dose of 450 mg/kg intraperitoneally (Sigma-Aldrich Chemical Co., St. Louis, MO, USA) and placed on a homeothermic blanket (Temperature Control Unit HB 101/2, Letica Scientific Instruments, Barcelona, Spain) in a supine position.…”
Section: Methodsmentioning
confidence: 99%
“…The studies performed on the two-vessel GCI model in gerbils [ 28 ] and mice [ 27 ] have shown neuroprotective effect of fluoxetine in the hippocampus. Preliminary results of our study [ 10 ] based on the rat three-vessel occlusion GCI model [ 30 , 31 ] have shown a decrease in the number of immature neurons in the DG after fluoxetine treatment at later observation times (30 days). Clearly, these limited observations do not provide a complete picture of a potential therapeutic effect of fluoxetine in GCI and warrant further studies.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation